2015
DOI: 10.1161/hypertensionaha.115.05961
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Predisposition to Higher Blood Pressure Increases Risk of Incident Hypertension and Cardiovascular Diseases in Chinese

Abstract: Recently, GWAS in East Asian and Chinese not only replicated previously reported BP loci in European populations but also identified several East Asian-specific variants for BP, 4,12 which suggested that both shared and population-specific BP susceptibility were commonly present. Moreover, besides genetic heterogeneity, there are marked differences between Chinese and Europeans in environmental exposure factors, including weight, diet, physical activity, obesity, alcohol drinking, and Abstract-Although multipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 28 publications
1
29
0
Order By: Relevance
“…The number of SNPs used in these studies ranged from 2 to 32 ( S2 Table ). The AUC or C-statistic of models[ 11 , 21 ] including GRS were superior compared to those without GRS (C-index change = 0.3%–0.5%; p <0.05). Twelve studies proposed to build models with logistic regression, 7 with COX regression, 6 with Weibull regression, and 1 with linear regression.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…The number of SNPs used in these studies ranged from 2 to 32 ( S2 Table ). The AUC or C-statistic of models[ 11 , 21 ] including GRS were superior compared to those without GRS (C-index change = 0.3%–0.5%; p <0.05). Twelve studies proposed to build models with logistic regression, 7 with COX regression, 6 with Weibull regression, and 1 with linear regression.…”
Section: Resultsmentioning
confidence: 97%
“…Two studies[ 17 , 31 ] defined isolated systolic hypertension as SBP ≥140 mmHg and DBP ≤ 90 mmHg, and isolated diastolic hypertension as DBP ≥ 90 mmHg and SBP ≤ 140 mmHg. Twenty studies used traditional factors only, and 6 studies[ 11 , 14 , 16 , 19 , 21 , 26 ] also included Genetic Risk Score (GRS) factors (indeed, 2 studies[ 19 , 26 ] used genetic risk factors exclusively). The common predictors included in most models were age, gender, BMI, SBP, DBP, and parental history of hypertension.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypertension, also known as high or raised blood pressure, is a condition in which the blood vessels have persistently raised pressure [1]. It is a global public health issue, as well as an important factor for cardiovascular diseases [2][3][4]. It has been reported that one in four men and one in five women have raised blood pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Hypertension is believed as a significant risk factor for cardiovascular disease (CVD), and has brought heavy economic burden to individuals, families, and society 1 4 . It is a great challenge for public health worldwide, because of its high prevalence, which accounts for nearly half of the cardiovascular morbidity and mortality in the world 5 , 6 .…”
Section: Introductionmentioning
confidence: 99%